Transparansi Pengelolaan Zakat dalam Meningkatkan Kepercayaan Muzakki pada UPZ di Desa Gunung Tua Kecamatan Ulu Sosa Kabupaten Padang Lawas - Junda Harahap; Indah Permatasari Siregar; Nur Jannah Nasution (Dirosah Islamiyah, 2026)
This study aims to the transparency of zakat management in increasing the trust of muzakki in UPZ and the factors that influence the trust of muzakki in UPZ Gunung Tua Village, Ulu Sosa District, Padang Lawas Regency. This research is a qualitative research. The data collection technique in this study used interview and observation techniques with the Head of UPZ, Deputy Head of UPZ and muzakki of Gunung Tua Village. The results of the study indicate that transparency practices at UPZ include honesty in reporting, trustworthiness in fund management, fairness in distribution, and openness of information to the public. Islamic values such as shidq (honesty), amanah (responsibility), and 'adl (justice) are the main foundations in carrying out zakat management tasks. Muzakki feel more confident and comfortable paying their zakat through UPZ because they feel indirectly involved in an open and responsible management process. Thus, it can be concluded that the higher the level of transparency applied, the higher the level of trust of muzakki in UPZ. Transparency is not only limited to administrative reporting, but also a real implementation of sharia principles in zakat management.